Bridging the funding gap for National Aids Council - Ganda, Barbara (Midlands State University, 2017)
The research project is about bridging the funding gap for National AIDS Council. The major objective of the study was establishment of the existence of the funding policy if in existence, how it was constituted, frequency of reviews, implementing guidelines and controls in place, its relevance in meeting new and changing needs of the organization. Research data was collected through questionnaires and interviews and was collected from directors, middle management and finance and administration staff. The major findings were that the funding policy was in existence as a blueprint and is communicated to employees. There was involvement of stakeholders in policy formulation, the policy however was not reviewed regularly to consolidate new best funding initiatives as well as to meet new needs of the organization and clientele. The major recommendations made included that NAC must review policy regularly and make use of the TRIPS agreement in acquisition of drugs as well as lobby through the Ministry of Health and Child Care.